A quantum chemistry study of Ds–Pa unnatural DNA base pair. Issue 4 (9th April 2012) - Otsuka, Takao; Miyazaki, Tsuyoshi; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract We have performed density functional theory and MP2 calculations of the unnatural DNA base pair, Ds–Pa, (7‐(2‐thienyl)‐imidazo[4, 5‐b]pyridine (Ds) and pyrrole‐2‐carbaldehyde (Pa)) in the gas phase. By calculating the interaction energy curve of Ds–Pa pair as a function of intermolecular distance, we have found that the interaction energy between Ds and Pa molecules is very weak. The detailed analysis of the structural properties of the optimized Ds–Pa pair has been also used and compared with those of A–T and G–C natural base pairs. These results clearly show that the Ds–Pa pair does not have any hydrogen bonds and suggest that the pair selectivity in the Ds–Pa pair mainly comes from the interaction of Ds or Pa molecules with other parts in DNA or RNA, such as upper or lower natural bases, sugar phosphate backbones, and water molecules. © 2012 Wiley Periodicals, Inc.